Toxicological Safety Evaluation in Acute and 21-Day Studies of Ethanol Extract from Solanum lyratum Thunb. (31st March 2022) - Guo, XiaoHua; Weng, LianJin; Yi, LiTao; Geng, Di
Abstract : Solanum lyratum (Solanaceae) is a traditional Chinese medicine widely used to remedy cold fever, damp-heat jaundice, herpes, and nephritis dropsy. Despite its obvious therapeutic advantages, few toxicological studies have involved the efficacy and safety of its long-term treatment. To investigate the acute and subchronic toxicity of the extract of 75% ethanol extract of whole Solanum lyratum (ESL) after oral administration in mice. In acute toxicity experiment, mice were intragastric administration with ESL at doses of 1000, 2000, 3000, 4000, or 5000 mg/kg for 1 day. In a subchronic toxicity experiment, mice were intragastrically administration with ESL at doses of 180, 360, and 720 mg/kg and 0.9% saline for 21 days. Weight gain, hematological, biochemical, and histopathological analysis of vital organs were evaluated. The presence of aristolochic acid I in ESL was studied using UPLC-QTOF-MS. Phytochemical analysis indicated that the presence of aristolochic acid I in ESL was 0.0025 mg/g. This relatively low concentration is not enough to cause toxicity. In the acute toxicity experiment, neither mortality nor clinical alterations were shown, except for the mild transient diarrhea at 5000 mg/kg. So the LD50 value of ESL was assessed to be more than 5000 mg/kg. In the subchronic toxicity experiment, neither mortality nor treatment-related clinical signs were observed. There was a significant increase in body weight, hemoglobin (HB), and urea nitrogen (BUN) after administration with ESL at 180 mg/kg. In addition, the weight of the stomach was increased and the hematocrit (HCT) was decreased after administration with ESL at 360 mg/kg. The changes were not considered treatment-related toxicological effects because the toxicity and histopathological analysis indicate that the extracts are safe for oral administration.